Acute Pancreatitis in a Patient With Ulcerative Colitis on Vedolizumab. Issue 5 (26th February 2020) - Lin, Elissa; Katz, Seymour
Abstract : Vedolizumab is a humanized monoclonal antibody that is approved for treatment of patients with moderate to severe ulcerative colitis and is thought to be both safe and effective. We present a case of vedolizumab-associated acute pancreatitis in an ulcerative colitis patient.